Uncommon Anatomic Predisposition to Myocardial Infarction: A Case of Coronary Artery Ectasia - Ghazzal, Amre (Cureus, 2020)
Coronary artery ectasia (CAE) is a recognized cause of acute coronary syndrome (ACS), and can be associated with life-threatening complications, including thrombus formation with consequent distal coronary artery embolization. Several studies have demonstrated a higher incidence of cardiovascular adverse events and cardiac death in patients with CAE or coronary artery aneurysms compared to those without such abnormalities. Management of symptomatic CAE is similar to coronary artery disease (CAD), where guideline-directed medical therapy is indicated due to coexistence of CAD with acquired CAE. Percutaneous coronary intervention can be attempted; however, it is challenging, as it is associated with lower procedural success, higher rates of stent thrombosis, and repeat revascularization.